Venezuela a contracorriente: poesía, resistencia y diáspora (una muestra) - Gregory Zambrano (Caravelle)
The poetic discourse has portrayed in various ways the so-called “bolivarian revolution” in Venezuela. The social, economic, cultural and political transformations have severely affected the country since the beginning of the 21st century. This work intends to follow the main lines that arise from the thematic and discursive associations that poetry reveals as a critical stance, facing new referents.